Kajian Penerapan Pendaftaran Calon Siswa Baru Berbasis Mobile Andorid - Marisa Ayu Saphira; Dwiny Meidelfi; Aldo Erianda (Indonesian Society of Applied Science, 2020)
The development of information and communication technology is rapidly increasing, giving a very big influence for the world of information and telecommunications technology. One of them is used to facilitate the registration of prospective new students. During this time the process of registering new students in various schools is still manual. In this study the author tries to resolve the above problems by utilizing an information system based on Android mobile for the registration system of prospective new students based on Android mobile to increase the effectiveness and flexibility of the school system. In the study of android applications used in the development of systems where new learners can input data through mobile phones. The study was conducted from the stages of needs analysis, design, implementation, to system testing. The purpose of this application is so that it can facilitate prospective new students in registering and the School in conducting and managing new student registration data.